Designing a communication plan for the effective promotion of breastfeeding - Soliva, Kiara Elise Y. (2019)
In this study, the constructs of the Integrated Behavior Model (IBM) were examined in order to assess the key determinants of breastfeeding. Despite the establishment of many programs in the country, there is still a lack of comprehensive breastfeeding programs that take into consideration the numerous factors that are considered as barriers to breastfeeding together with the presence of ?support systems? who can assist them in breastfeeding. The Integrated Behavior Model (IBM) establishes that the main tenets of behavior are attitude, perceived norm, and personal agency. These were then measured through a survey questionnaire while baseline data about breastfeeding programs were gathered from L.A.T.C.H. Davao and the Barangay Nutrition Scholar (BNS). The resulting communication plan made use of the ROPE process which stands for Research, Objectives, Programming, and Evaluation. The objectives are based on the information gathered from the formative research portion together with the data gathered through the interviews and specific strategic communication tools were designed for the effective promotion of breastfeeding.